2015
DOI: 10.1073/pnas.1502104112
|View full text |Cite
|
Sign up to set email alerts
|

Color preference in red–green dichromats

Abstract: Around 2% of males have red-green dichromacy, which is a genetic disorder of color vision where one type of cone photoreceptor is missing. Here we investigate the color preferences of dichromats. We aim (i) to establish whether the systematic and reliable color preferences of normal trichromatic observers (e.g., preference maximum at blue, minimum at yellow-green) are affected by dichromacy and (ii) to test theories of color preference with a dichromatic sample. Dichromat and normal trichromat observers named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 37 publications
3
46
2
Order By: Relevance
“…For example, the activation of the yellow-blue system was a significant predictor and explained almost two thirds of the variance (R 2 = .61) in protanopes' preference for the full color set and more than three quarters of the preference for saturated (R 2 = .76) and light (R 2 = .88) colors (see Table 1 in Ref. [20]). Besides, this novel study demonstrated that the fluency of processing also underlies males' preference (either normal trichromats or dichromats): there was a higher preference for the colors named more accurately, quicker, more consistently and with greater consensus in normal trichromatic males and dichromatic males but not in normal trichromatic females.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the activation of the yellow-blue system was a significant predictor and explained almost two thirds of the variance (R 2 = .61) in protanopes' preference for the full color set and more than three quarters of the preference for saturated (R 2 = .76) and light (R 2 = .88) colors (see Table 1 in Ref. [20]). Besides, this novel study demonstrated that the fluency of processing also underlies males' preference (either normal trichromats or dichromats): there was a higher preference for the colors named more accurately, quicker, more consistently and with greater consensus in normal trichromatic males and dichromatic males but not in normal trichromatic females.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Model B includes a third variable: the aforementioned residual red-green discrimination. Section 4 deals with an emotional aspect related to color, describing color preferences in red-green dichromats and comparing them to the preferences of normal trichromats [20]. Finally in Section 5, we will summarize the most important conclusions of our research on red-green dichromats.…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Further study by Álvaro et al (2015) investigated the color preference of red-green dichromats. The results suggested that dichromats have different preferences than that of those with normal color vision; dichromats rated yellow best, unlike normal individuals.…”
Section: Introductionmentioning
confidence: 99%